1990
DOI: 10.1149/1.2086796
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Reduction of Carbon Dioxide on Various Metal Electrodes in Low‐Temperature Aqueous  KHCO 3 Media

Abstract: Electrochemical CO2 reduction was investigated on 32 metal electrodes in aqueous KHCO3 medium. The current efficiency of CO2 reduction on Ni, Ag, Pb, and Pd increases significantly with lowering the temperature. The ratio of reduction products are also changed by lowering temperature. Potential dependence of HCOOH and H2 on an Hg electrode supports the electron transfer mechanism for HCOOH production. Formation of methane and ethylene is observed on almost all metal electrodes used, although the efficiency is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
313
4
2

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 471 publications
(329 citation statements)
references
References 14 publications
10
313
4
2
Order By: Relevance
“…Here, an indium plate (99.9999%, Nilaco, Japan) was chosen as the cathode for CO 2 reduction, while a nitride semiconductor device was placed at the anode. In the electrochemical reduction of CO 2 , indium appears, as noted in previous electrochemical studies, 26,27 to behave as a selective catalytic electrode for HCOOH production, although it needs a large overpotential for the reaction. To accomodate the large cathodic potential, we applied AlGaN layer on the surface of photo-electrode as described above, in which the potential of cathode side can be lifted up compared with the case of conventional GaN photo-electrode.…”
Section: Methodsmentioning
confidence: 69%
“…Here, an indium plate (99.9999%, Nilaco, Japan) was chosen as the cathode for CO 2 reduction, while a nitride semiconductor device was placed at the anode. In the electrochemical reduction of CO 2 , indium appears, as noted in previous electrochemical studies, 26,27 to behave as a selective catalytic electrode for HCOOH production, although it needs a large overpotential for the reaction. To accomodate the large cathodic potential, we applied AlGaN layer on the surface of photo-electrode as described above, in which the potential of cathode side can be lifted up compared with the case of conventional GaN photo-electrode.…”
Section: Methodsmentioning
confidence: 69%
“…In recent years, different metallic electrodes have been studied for the electrochemical reduction of carbon dioxide, since the product distribution strongly depends on the used material, surface metallic arrangement, and surface energy [11][12][13][14][15][16][17]. Copper has been found to be one of the most effective electrode materials for the CO 2 reduction process at atmospheric pressure and room temperature in aqueous solutions [11,12,16].…”
Section: Introductionmentioning
confidence: 99%
“…Copper has been found to be one of the most effective electrode materials for the CO 2 reduction process at atmospheric pressure and room temperature in aqueous solutions [11,12,16]. On the other hand, CO 2 is hardly reduced on group VIII-X metal electrodes such as Fe, Co, and Ni, under similar conditions [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Also, similar to Sn catalysts, bulk Pb also exhibits av arying FE HCOO À due to the different surfacet reatments employed, signifying the importanceo fs urface morphology and chemical composition in catalyzing CO 2 RR. [145,146] In fact, the importance of ak inetically stable thin layer of PbO x was determined to be intrinsically relatedt ot he suppression of HER, while resulting in high FE HCOO À as indicated by the in situ ATIR studies reported by Bocarsly and co-workers. [147] Nevertheless,t here are some major limitations with Pb electrodes.…”
Section: Pbmentioning
confidence: 99%